2011
DOI: 10.17221/105/2011-pse
|View full text |Cite
|
Sign up to set email alerts
|

Use of dredged sediments on agricultural soils from viewpoint of potentially toxic substances

Abstract: A set of 29 pond sediments samples was collected. The sediments were separated into three groups, field, village, and forest pond sediments. The sediment samples were taken from pond bottoms and sediment heaps. The sediment characteristics (pH, CEC, Al-exchangeable, C ox , humus substances), the content of potentially toxic elements and persistent organic pollutants were analysed in the sediments and compared between sediment groups. The comparison of sediment contamination with Czech legislation for sediment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 13 publications
0
3
0
2
Order By: Relevance
“…In our previous study, fine fractions of sediments were demonstrated to play a dominant role in the distribution of dioxins in Rybnik Reservoir (Baran et al 2019c ). Vácha et al ( 2011 ) and Lee et al ( 2006 ) also observed a poor relation between the concentration of organic pollutants and the content of TOC in the sediment. Moreover, Lee et al ( 2006 ) suggested that the concentration of dioxins in silt and clay particles was up to 16 times higher than in sand or coarse.…”
Section: Discussionmentioning
confidence: 94%
“…In our previous study, fine fractions of sediments were demonstrated to play a dominant role in the distribution of dioxins in Rybnik Reservoir (Baran et al 2019c ). Vácha et al ( 2011 ) and Lee et al ( 2006 ) also observed a poor relation between the concentration of organic pollutants and the content of TOC in the sediment. Moreover, Lee et al ( 2006 ) suggested that the concentration of dioxins in silt and clay particles was up to 16 times higher than in sand or coarse.…”
Section: Discussionmentioning
confidence: 94%
“…Além disso, simulações da disposição de sedimentos de dragagem em Latossolos e Chernossolos são frequentemente realizadas em Horizonte B, tendo em vista cenários hipotéticos de disposição visando à recuperação de áreas degradadas (Cesar et al, 2014). A escolha pelo Latossolo se deve ao fato de que esta é a classe de solo mais abundante no Brasil e amplamente utilizada na agricultura e ao uso potencial de sedimentos dragados como fertilizante nestes solos (Vacha et al, 2011). O Chernossolos, por outro lado, tem distribuição espacial mais restrita no Brasil, mas são comumente utilizados em agriculturas de lavouras intensivas, principalmente no sul no Brasil.…”
Section: Materials E Métodos 21 Amostrasunclassified
“…A dragagem desses sistemas aquáticos é frequentemente requerida com o objetivo de restaurar a navegabilidade de corpos hídricos assoreados, bem como de prevenir e/ou atenuar os impactos oriundos da eutrofização, da proliferação de patógenos e da contaminação por metais e compostos orgânicos (Ho et al 2002, Munns et al 2002, Machado et al 2011. Nesse contexto, a disposição sustentável dos sedimentos de dragagem (via de regra, na ordem de milhões de m 3 ) torna-se temática de extrema relevância e alguns autores descrevem o reaproveitamento desses materiais na construção civil, no engordamento de praias e como insumo na agricultura (Ho et al 2002, Munns et al 2002, Vacha et al 2011.…”
Section: Introductionunclassified